STRENGTH OF THE WEB OF I-BEAMS OF REINFORCED CONCRETE UNDER THE ACTION OF SHEAR FORCE - Klymov, Yuliy (Sworld-Us Conference proceedings, 2025)
All existing methods for calculating the strength of reinforced concrete elements are based on experimentally established possible types of element failure under certain forces caused by external forces. The resistance of reinforced concrete elements to s